THE WIND INFLUENCES OVER THE POLLUTION CONCENTRATION IN THE URBAN ENVIRONMENT IN THE CITY OF CLUJ NAPOCA - Horia CRIVEANU; Ana HORHAT; Anca HUSTI; Cosmin OANA; Dorin-George BOB; Camelia ȘCHEAU-MISIRIANTU (Agricultura, 2019)
Currently, 55% of the world's population lives in urban areas, a proportion that is expected to increase by 2050 to 68% (ec.europa.eu). Urban air quality continues to be an essential health issue, accompanied by the fact that one of the fundamental global sources of air pollution in the city is traffic emissions (Kumar et al., 2015). The purpose of this study is to highlight the effects on wind flows in an urban environment, especially on atmospheric pollutants. For this purpose, the main arteries of Cluj-Napoca were selected as a case study, Marasti -BRD, - Orthodox Cathedral- St. Michael's Church - Calea Motilor - Calea Manastur. These areas were chosen because they were monitored by different measuring instruments from several / various locations, which provided input data for the present study. Likewise, two situations were considered regarding the winds in the municipality of Cluj, from a seasonal point of view: summer and winter. Were distinguished 11 sectors on the west-east alignment, having specific characteristics, depending on the existing buildings and spaces. There were significant differences between the wind rose in the winter and the summer. This results leads to local air movements more pronounced than in winter period,  having as an effect a quasi-constant state of pollution. As a result, it is necessary to "help" the improvement of air quality by planting a mix of arboreal species in these areas, which we call „oxygen fountains”.